The prevalence of gingivitis around anterior acrylic crown restorations done in the UP College of Dentistry, SY 1989-1990 - Lozada, Lawrence M.
This study was conducted to determine the prevalence of gingivitis among anterior acrylic crown restorations done in the UP College of Dentistry SY 1989-1990. Majority of the 51 crowns assessed in this study were observed to have developed mild gingivitis. No cases of severe gingivitis were noted. Only 1 crown was observed to be overcontoured. Significant relationships between plaque and gingivitis and the presence of crowns and gingivitis were established but no relationship between plaque accumulation and the presence of crowns was observed.